Odpowiedź:
a)
7x - 1 = 7 * (-4) - 1 = -28 - 1 = -29
dla x = -4
7x - 1 = 7 * 5 - 1 = 35 - 1 = 34
dla x = 5
7x - 1 = 7 * 0 - 1 = -1
dla x = 0
b)
6 - x = 6 - 3 = 3
dla x = 3
6 - x = 6 - (-2) = 6 + 2 = 8
dla x = -2
6 - x = 6 - 0 = 6
dla x = 0
c)
x(9 - x) = 5(9 - 5) = 5 * 4 = 2-
dla x = 5
x(9 - x) = 8(9 - 8) = 9 * 1 = 9
dla x = 8
x(9 - x) = -3(9 + 3) = -3 * 12 = -36
dla x = -3
d)
8 - 4x = 8 - 4 * 3 = 8 - 12 = -4
dla x = 3
8 - 4x = 8 - 4 * (-3) = 8 + 12 = 20
dla x = -3
8 - 4x = 8 - 4 * 1/4 = 8 - 1 = 7
dla x = 1/4
Szczegółowe wyjaśnienie: